Assessment of quality improvement priorities to improve care delivery for patients with ovarian cancer. Issue 28 (1st October 2022) - Smeltzer, Matthew; Senter, Leigha; Thaker, Premal H.; Black, Destin; Blank, Stephanie V.; Bires, Jennifer; Prescott, Lauren S.; Bupathi, Manojkumar; Drescher, Charles W.; Cliby, William; Yemelyanova, Anna; Effange, Doreen; et al.
Abstract : 307 Background: In the US, more than 12, 000 people die from ovarian cancer annually. Although new treatments have recently become available, ovarian cancer care delivery remains suboptimal. The Association of Community Cancer Centers (ACCC) developed a series of initiatives to improve the quality of care for patients with ovarian cancer. In Phase I, ACCC evaluated the needs of cancer programs, conducted 3 quality improvement (QI) workshops, and developed expert-driven Quality of Care recommendations to aid cancer programs in self-assessment and quality improvement. In Phase II, ACCC invited programs to self-assess their level of care using the Quality of Care recommendations. Methods: In 2022, ACCC surveyed 7 ovarian cancer programs across the US. Developed by a multidisciplinary expert steering committee, the 26-question survey assessed the patient populations served, services provided, diagnostic evaluations performed, access to molecular testing, and a self-assessment of quality care delivery and interest in conducting QI projects related to self-identified needs. The survey was administered in Qualtrics and summarized using descriptive statistics. Results: Surveys were completed by 1 community, 2 comprehensive community, 2 hospital-associated, 1 academic comprehensive, and 1 NCI-designated comprehensive cancer programs. The median annual ovarian cases was 40 [range: 2 to 68]. The 7 programs serve diverse racial/ethnic distribution of patients with ovarian cancer ranging from 55% Black to 60% Asian and 30% Pacific Islander. Five programs have a multidisciplinary team for ovarian cancer. All 5 multidisciplinary teams included gynecologic oncology and pathology; 3 teams also included medical oncology and or radiology colleague(s). Sites assessed their level of care for 7 domains of quality care from 1 (lowest) to 5 (highest). The average score was 4.0 for Care Coordination and Patient Education, Treatment Planning, and Disease Surveillance. Diagnosis and Initial Management scored on average 3.8, Equity in Care 3.25, Prevention and Screening 3.25, and Quality of Life 3.2. Sites ranked areas of interest for future QI projects (1 = area of most interest, 7 = area of least interest). The highest ranked domains were Care Coordination and Patient Education as well as Diagnosis and Initial management (average rankings 2.8). These were followed by Quality of Life (average 3.0), Prevention and Screening (Average 3.8), Treatment Planning (Average 4.4), Equity in Care (Average 5.0), and Disease Surveillance (Average 6.2). Conclusions: This assessment will be used to identify 4 additional sites for Phase II QI workshops. Findings from these projects will be combined, summarized, and disseminated to inform future education opportunities and QI initiatives. This initiative aims to help organize and standardize the care of patients with ovarian cancer and improve patient care coordination.